LINKING LOGAN: Reconnecting the Logan Triangle - Walls, Natalie; Wackerla, Lance; Roberts, Gage; Pileggi, John; Jennings, Kylee (My University, 2023)
The purpose of this project is to reinvigorate the Logan Neighborhood through the revitalization and reengagement of the Logan Triangle. Through traditional row housing, multi-family apartment complexes, investments in local businesses with prime retail space; combined with a multi-faceted community center, exceptional amphitheater space, and extensive greenspace, we look to turn Logan Triangle from a blighted oversight into a point of pride for the Logan Neighborhood.